Maltose binding protein-fusion enhances the bioactivity of truncated forms of pig myostatin propeptide produced in E. coli - Lee, Sang Beum (PLoS One, 2017)
Myostatin (MSTN) is a potent negative regulator of skeletal muscle growth. MSTN propeptide (MSTNpro) inhibits MSTN binding to its receptor through complex formation with MSTN, implying that MSTNpro can be a useful agent to improve skeletal muscle growth in meat-producing animals. Four different truncated forms of pig MSTNpro containing N-terminal maltose binding protein (MBP) as a fusion partner were expressed in E. coli, and purified by the combination of affinity chromatography and gel filtration. The MSTN-inhibitory capacities of these proteins were examined in an in vitro gene reporter assay. A MBP-fused, truncated MSTNpro containing residues 42–175 (MBP-Pro42-175) exhibited the same MSTN-inhibitory potency as the full sequence MSTNpro. Truncated MSTNpro proteins containing either residues 42–115 (MBP-Pro42-115) or 42–98 (MBP-Pro42-98) also exhibited MSTN-inhibitory capacity even though the potencies were significantly lower than that of full sequence MSTNpro. In pull-down assays, MBP-Pro42-175, MBP-Pro42-115, and MBP-Pro42-98 demonstrated their binding to MSTN. MBP was removed from the truncated MSTNpro proteins by incubation with factor Xa to examine the potential role of MBP on MSTN-inhibitory capacity of those proteins. Removal of MBP from MBP-Pro42-175 and MBP-Pro42-98 resulted in 20-fold decrease in MSTN-inhibitory capacity of Pro42-175 and abolition of MSTN-inhibitory capacity of Pro42-98, indicating that MBP as fusion partner enhanced the MSTN-inhibitory capacity of those truncated MSTNpro proteins. In summary, this study shows that MBP is a very useful fusion partner in enhancing MSTN-inhibitory potency of truncated forms of MSTNpro proteins, and MBP-fused pig MSTNpro consisting of amino acid residues 42–175 is sufficient to maintain the full MSTN-inhibitory capacity.